2020
DOI: 10.1021/acs.jafc.0c01365
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Crystal Structure, and Antimicrobial Evaluation of 6-Fluoroquinazolinylpiperidinyl-Containing 1,2,4-Triazole Mannich Base Derivatives against Phytopathogenic Bacteria and Fungi

Abstract: A total of 20 1,2,4-triazole Mannich base derivatives bearing the 6-fluoroquinazolinylpiperidinyl moiety were designed, synthesized, and evaluated as antimicrobial agents against phytopathogenic bacteria and fungi according to the molecular hybridization strategy. Of note, the structure of target compound 4h was clearly confirmed through single-crystal X-ray diffraction analysis. The turbidimetric assays indicated that some compounds exhibited excellent antibacterial efficacies in vitro against Xanthomonas ory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…On the other hand, 1,2,4-triazole, as an important kind of heterocyclic nitrogen compounds, is a versatile lead molecule and usually employed to design potential bioactive agents whether in the field of pesticides or medicine. This molecule and its derivatives have received considerable attention owing to a wide range of biological activities, such as anticancer ( Li et al, 2016 ; El-Sherief et al, 2018 ; Hou et al, 2019 ), antibacterial ( Gao et al, 2019 ; Shi et al, 2020 ), anti-inflammatory ( Abdel-Aziz et al, 2014 ), antiviral ( Chen et al, 2019 ), antifungal ( Xu et al, 2011 ), antitubercular ( Karczmarzyk et al, 2020 ) and other biological activities ( Mustafa et al, 2019 ; Liao et al, 2020 ; Peng et al, 2021 ). Our research group has reported the synthesis of two series of 1,2,4-triazole derivatives with potent antifungal activities ( Lin et al, 2017 ; Lin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 1,2,4-triazole, as an important kind of heterocyclic nitrogen compounds, is a versatile lead molecule and usually employed to design potential bioactive agents whether in the field of pesticides or medicine. This molecule and its derivatives have received considerable attention owing to a wide range of biological activities, such as anticancer ( Li et al, 2016 ; El-Sherief et al, 2018 ; Hou et al, 2019 ), antibacterial ( Gao et al, 2019 ; Shi et al, 2020 ), anti-inflammatory ( Abdel-Aziz et al, 2014 ), antiviral ( Chen et al, 2019 ), antifungal ( Xu et al, 2011 ), antitubercular ( Karczmarzyk et al, 2020 ) and other biological activities ( Mustafa et al, 2019 ; Liao et al, 2020 ; Peng et al, 2021 ). Our research group has reported the synthesis of two series of 1,2,4-triazole derivatives with potent antifungal activities ( Lin et al, 2017 ; Lin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For example, rice sheath blight, bacterial fruit spot of melon and bacterial blight of rice, and so forth, are difficult to control in agricultural production. [3][4][5] Rice sheath blight is one of the most widely distributed in rice and caused by RS infection. It mainly infects the leaf sheath and leaf of rice, and its symptom change from an early water damage disease spot to a moire shape.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently, some researchers took advantage of hybridization strategy that active thiazole segment was spliced with other pharmacophore (eg. Piperidine [ , pyrazole, quinazoline, and alkaloid) [17][18][19][20][21] to design novel compounds, and further indeed discovered several potential molecules with fungicidal activities.…”
Section: Introductionmentioning
confidence: 99%